Intellectual philanthropy : the seduction of the masses - Vialette, Aurélie (Purdue studies in Romance literatures., 2018)
"Intellectual Philanthropy: The Seduction of the Masses by Aurélie Vialette examines the practice of philanthropy in modern Spain. Through detailed studies of popular music, collective readings, dramas, working-class manuals, and fiction, Vialette reveals how depictions of urban philanthropic activities can inform our understanding of interactions in the economic, cultural, religious, and educational spheres, class power dynamics, and gender roles in urban Spanish society"--